Persepsi Mahasiswa terhadap Ruang Terbuka Hijau Ideal di Kampus Undip Tembalang - Iras Nurlita Fitriani; Retno Susanti (Teknik PWK (Perencanaan Wilayah Kota), 2020)
Diponegoro University is a university with 73% of green open space. Green open space is good for supporting physical and mental health and academic performance of students. But in order for GOS to be used optimally, it is necessary to provide the suitable GOS. The purpose of this study is to find out what students' perceptions of the ideal green space. This research method uses a mixed approach. The analysis is carried out by performing content analysis and frequency distribution analysis. Result shows that there are 47 variations of ideal GOS criteria according to Undip Tembalang students. Then students are asked to choose one of the 6 GOS which they think is the most ideal. Analysis of the criteria that affect the selection of each GOS shows that the ideal GOS in Tembalang Undip Campus is based on 32 criteria. In addition, the findings show that the activities that are mostly carried out by students in GOS are physical activities and social interactions. This becomes the basis in determining the ideal green space on the Undip Tembalang Campus which show that the Undip Reservoir Area is the most ideal green space at this time.